The potential of interactive multimedia with contextual teaching and learning approaches in mathematics learning: a systematic literature review - Pratiwi, Khairunnisa Hanan; Situmorang, Robinson -; Iriani, Tuti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to determine the potential and characteristics of interactive multimedia with an effective Contextual Teaching and Learning (CTL) approach in elementary school mathematics learning through a Systematic Literature Review (SLR). A total of 18 relevant studies were analyzed in this study, which consisted of journal articles published in 2013-2023. Scientific journals or conference proceedings are used indexed by Scopus Q1-Q4. The exclusion criteria in this article are articles that do not have a complete structure, review articles or conceptual articles that do not report the results of empirical research. The results of the analysis show that interactive multimedia with the CTL approach has great potential in improving the learning outcomes, motivation, engagement, and understanding of mathematical concepts of elementary school students. CTL allows students to see how mathematical concepts can be applied in everyday life, making the learning process more relevant and engaging. Characteristics of interactive multimedia with an effective CTL approach include the use of rich and relevant visuals to real-world contexts, interactivity that allows active exploration, authentic presentation of problems, constructive feedback, scaffolding that suits the needs of students, and the integration of elements of art and aesthetics. The implementation of interactive multimedia with the CTL approach also has challenges, such as the availability of technology infrastructure and teacher competence. This study implies that teachers and researchers need to realize that the design and use of interactive multimedia with the CTL approach can effectively improve the quality of mathematics learning in elementary school.